COPI buds 60-nm lipid droplets from reconstituted water-phospholipid-triacylglyceride interfaces, suggesting a tension clamp function - Thiam, Abdou Rachid; Antonny, Bruno; Wang, Jing; Delacotte, Jérôme; Wilfling, Florian; Walther, Tobias C.; Beck, Rainer; Rothman, James E.; Pincet, Frédéric (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Intracellular trafficking between organelles is achieved by coat protein complexes, coat protomers, that bud vesicles from bilayer membranes. Lipid droplets are protected by a monolayer and thus seem unsuitable targets for coatomers. Unexpectedly, coat protein complex I (COPI) is required for lipid droplet targeting of some proteins, suggesting a possible direct interaction between COPI and lipid droplets. Here, we find that COPI coat components can bud 60-nm triacylglycerol nanodroplets from artificial lipid droplet (LD) interfaces. This budding decreases phospholipid packing of the monolayer decorating the mother LD. As a result, hydrophobic triacylglycerol molecules become more exposed to the aqueous environment, increasing LD surface tension. In vivo, this surface tension increase may prime lipid droplets for reactions with neighboring proteins or membranes. It provides a mechanism fundamentally different from transport vesicle formation by COPI, likely responsible for the diverse lipid droplet phenotypes associated with depletion of COPI subunits.
Gesehen am 03.02.2022